PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DI BANDARA - Mahrawati Mahrawati (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
In business aviation industry, providing and performing high quality service is critical in order to give satisfaction to the customers. The service quality has become the basic in maintaining the improvement to fulfill customer satisfaction regarding to their expectations, wants, and needs. For customers expect to find what they want where they expect to, and they also need to fulfill the expectation in having a satisfying experience. This research study was conducted for two objectives, namely (a) to find out and anlyze the effect of service quality according to the response capacity, insurance, physical evidence, empathy, and competency on the customer satisfaction of the Cilik Riwut Airport customers in Palangka Raya, (b) to find out and analyze the dominance of service quality in customer satisfaction of the Cilik Riwut Airport customers in Palangka Raya. This study obtained physical evidence (X3) in relevance to the score B= 0.309 as the result in which can be inferred that the independent variable (X) stands for the service quality, showed a dominant and significant effect on customer satisfaction of the Cilik Riwut Airport customers in Palangka Raya. Therefore, this result accepted the second hypothesis (H1) as it rejected H0. In other words, the result indicated and proved that the dominant physical evidence of service quality affects the customer satisfaction of the Cilik Riwut Airport customers in Palangka Raya.